Joint strategic energy and river basin planning to reduce dam impacts on rivers in Myanmar. (7th May 2021) - Schmitt, Rafael J P; Kittner, Noah; Kondolf, G Mathias; Kammen, Daniel M
Abstract: Tackling climate change and human development challenges will require major global investments in renewable energy systems, including possibly into large hydropower. Despite well-known impacts of hydropower dams, most renewable energy assessments neither account for externalities of hydropower nor evaluate possible strategic alternatives. Here we demonstrate how integrating energy systems modeling and strategic hydropower planning can resolve conflicts between renewable energy and dam impacts on rivers. We apply these tools to Myanmar, whose rivers are the last free-flowing rivers of Asia, and where business-as-usual (BAU) plans call for up to 40 GW of new hydropower. We present alternative energy futures that rely more on scalable wind and solar, and less on hydropower (6.7–10.3 GW) than the BAU. Reduced reliance on hydropower allows us to use river basin models to strategically design dam portfolios for minimized impact. Thus, our alternative futures result in greatly reduced impacts on rivers in terms of sediment trapping and habitat fragmentation, and result in lower system costs ($8.4 billion compared to $11.7 billion for the BAU). Our results highlight specific opportunities for Myanmar but also demonstrate global techno-ecological synergies between climate action, equitable human development and conservation of riparian ecosystems and livelihoods.